Pembuatan Simulasi Interaktif “Perpindahan Panas (Konduksi, Konveksi, Radiasi)” Berbasis Aplikasi Qreatif Educative untuk Siswa Kelas 5 SD - Alifia Nida Safira Meidiah; Ika Putra Viratama (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2026)
The purpose of this study was to investigate how fifth-grade elementary school students can create and utilize interactive simulations on heat transfer (conduction, convection, and radiation) using the Qreatif Educative application. The background of this study stems from students' difficulty in understanding the abstract concept of heat transfer, which cannot be directly experienced. Therefore, interactive and concrete learning tools are needed to illustrate these concepts. The methodology of this study is a literature review, which includes collecting, evaluating, and integrating findings from previous studies relevant to the application of interactive simulations in science education. The findings of this study indicate that through dynamic representations of heat transfer events, interactive simulations based on the Qreatif Educative application can improve students' conceptual understanding, learning engagement, and scientific thinking skills. Furthermore, interactive simulations support visual and kinesthetic learning styles and are appropriate for the cognitive developmental characteristics of fifth-grade students who are at the concrete operational stage. Consequently, the use of interactive simulations based on Qreatif Educative is an effective alternative learning medium to enhance students' understanding of the concept of heat transfer, increase their enthusiasm for learning, and make science education more relevant, contextual, and creative.